2009
DOI: 10.1007/s00534-009-0079-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of preoperative dexamethasone in patients with laparoscopic cholecystectomy: a prospective randomized double-blind study

Abstract: The regimen we employed is safe and without apparent side effects. These results suggest that preoperative dexamethasone (8 mg) significantly reduces the incidence of PONV, pain, and fatigue after LC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 23 publications
4
48
0
6
Order By: Relevance
“…The results are similar with studies conducted by Fukami et al [8] and Lim et al [9] The mechanism of pain relief by dexamethasone is mainly provided by peripheral suppression of phospolipase enzyme, thereby significantly decreasing the products of cyclooxygenase and lipooxygenase pathways in the inflammatory response [8,10]. Additionally dexamethasone reduced bradykinin which reinforces pain in the inflamed tissues and operated area, and also the decreased concentration of nerve proteins secreted from the peripheral nerve system are involved in the analgesic effect [11].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results are similar with studies conducted by Fukami et al [8] and Lim et al [9] The mechanism of pain relief by dexamethasone is mainly provided by peripheral suppression of phospolipase enzyme, thereby significantly decreasing the products of cyclooxygenase and lipooxygenase pathways in the inflammatory response [8,10]. Additionally dexamethasone reduced bradykinin which reinforces pain in the inflamed tissues and operated area, and also the decreased concentration of nerve proteins secreted from the peripheral nerve system are involved in the analgesic effect [11].…”
Section: Discussionsupporting
confidence: 80%
“…Several clinical trials in many different surgical procedures evaluated the effects of a single dose of dexamethasone administered on post operative pain but have inconsistent findings [7,8]. Furthermore, there are very few articles on use of preoperative Dexamethasone for postoperative pain relief in the Indian Scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were obtained by Fukami et al who found that Dexamethasone significantly reduced postoperative pain and analgesic requirements after LC compared with the placebo group. [24] CONCLUSION The combination of dexamethasone plus metoclopramide reduces the intensity of nausea. Dexamethasone and Dexamethasone plus Metoclopramide was found more effective in preventing PONV and decreasing the requirement of rescue antiemetic than Metoclopramide or placebo.…”
Section: Discussionmentioning
confidence: 97%
“…[2,3,17,[20][21][22][23][24][25][26] Henzi et al analysed 17 studies comparing the efficacy of prophylactic Dexamethasone with a placebo for PONV, and found it more effective than placebo. [27] Conversely, Fujii et al conducted a study in women undergoing major gynaecological operations, and found that Dexamethasone at 8 mg dose alone did not reduce PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier there was not found a significant effect or no effect on postoperative nausea and vomiting and pain in studies. In the concept of enhanced recovery, the effects have been found 84 but Fukami et al found no effect in a randomized controlled trial 86 Another trial found that 8 mg dexamethasone preoperatively has no significant effect on reducing postoperative inflammatory response and also does not improve outcomes of colorectal surgery. 87 The analgesic effects of GCs are provided through inhibition of the phospholipase enzyme and accordingly blockage of both the cyclooxygenase and the lipoxygenase pathway in the inflammatory chain reaction.…”
Section: Preoperative Medicationmentioning
confidence: 98%